2010
DOI: 10.1080/10298436.2010.488729
|View full text |Cite
|
Sign up to set email alerts
|

X-ray fluorescence detection of waste engine oil residue in asphalt and its effect on cracking in service

Abstract: This paper documents the discovery of waste engine oil residues in pavements across Ontario, Canada. We have found that recovered asphalts from a large majority of poorly performing contracts test positive for zinc through X-ray fluorescence (XRF) analysis. In contrast, neither the aggregates nor any of the well-performing asphalts showed any signs of the metal. Since zinc dialkyldithiophosphates are universal additives in engine oils, we inferred that the use of waste oil residues in asphalt must be widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 20 publications
(40 reference statements)
2
39
0
Order By: Relevance
“…Within the last five years some researchers have raised concerns that the use of REOB in bitumen has led to early pavement cracking. Tests have been developed by Hesp and his co-workers to identify bitumen properties believed to be related to the presence of REOB and indicative of poor pavement performance (Hesp S. &., 2010) (Rubab, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Within the last five years some researchers have raised concerns that the use of REOB in bitumen has led to early pavement cracking. Tests have been developed by Hesp and his co-workers to identify bitumen properties believed to be related to the presence of REOB and indicative of poor pavement performance (Hesp S. &., 2010) (Rubab, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Hesp et al (Hesp andShurvell 2010, Burke andHesp 2011) has shown that the use of waste engine oil residue can be used to extend the binder performance grade. However, the use of such oils caused physical and chemical hardening of binder and premature excessive thermal cracking of asphalt pavements in Ontario province in Canada, and therefore the authors do not advise the use of WEO residue as rejuvenators.…”
Section: Performance Of Rejuvenated Mixesmentioning
confidence: 97%
“…rough X-ray fluorescence analysis in Canada, Hesp and Shurvell [9] confirmed that REOB can be used in asphalt binders and discussed the adverse effects of REOB on the early cracking of asphalt pavement. Rubab et al [10] conducted rolling thin film oven (RTFO) and pressure ageing vessel (PAV) tests after mixing REOB with two different types of asphalt binders in Canada and found that REOB may accelerate the oxidation speed of modified asphalt while improving the performance grade of asphalt binders.…”
Section: Introductionmentioning
confidence: 93%